Tragic Orpheus. Orpheus on the stage of the Old Attic Theater (Research Announcements "Heritage BG", 2025)
The article offers an analysis of the information about the figure of Orpheus on the stage of the Old Attic theater in the 5th century BC. They are systematized in several groups around the mythological motifs characterizing the Thracian musician: The magical power of Orpheus’ word-song; Orpheus enchanting wild animals, which is closely associated with the myth of the Argonauts; the myth of the katabasis of Orpheus. In ancient times, magic was almost always negatively associated with the religious practices of someone else, a foreigner, the Other. It is a term that distinguishes these practices from the norm and a means of defining theOtherness embodied in the figure of Orpheus. Along this line, the reserved and even negative attitude towards Orphism and the related religious movement in classical Athens developed. These characteristics transform the figure of the Thracian into inconsistent, conflicting with the canons of good tragedy, defined by Aristotle in his Poetics, and explain why it appears on the stage of the Old Attic theater unsystematically and in associative terms. References:Bogdanov, B. (1991). Orfey i drevnata mitologia na Balkanite. Sofia.Fol, V. (2020). Tayni obshtestva na trakite. Sofia.Lozanova, V. (2003). ΜΙΜΗΣΙΣ ΚΑΙ ΚΑΘΑΡΣΙΣ ili za prirodata na antichnia teatar. V: Godishnik na NBU. Departament „Sredizemnomorski iztochni izsledvania”. T. 1 (202). Sofia, 75-80.Lozanova-Stancheva, V. (2019). Sakralna infrastruktura v Pangeyskia region 6–5 v.pr.Hr. – Thracia, 24, 137-163.Lozanova-Stancheva, V. (2020). Stsenata „Orfey ukrotyava divite zhivotni“: mezhdu profannoto i sakralnoto. – Thracia, 25, 23-39.Aristophanes (1846). Aristophanis comoediae et deperditarum fragmenta ex nova recensione Guilelmi Dindorf. Parisiis.Aristotle (1932). Aristotle in 23 Volumes, Vol. 23, translated by W.H. Fyfe. Cambridge, MA, London.Bernabé, A. (2017). Orpheus in Apollodorus. In: Bernabe, Alberto. Apollodoriana. Ancient Myths, New Crossroads. Berlin, Boston, 113-125.Bond, G. W. (1963). Hypsipyle. London.Bremmer, J. N. (1991). From Guru to Gay. In: Bourgeaud, P. (Ed.). Orphisme et Orphée: en l’honneur de Jean Rudhardt. (Recherches et Rencontres, n° 3). Geneva, 13-30.Bremmer, J. N. (2008). Persian Magoi and the Birth of the Term ‘Magic’. In: Bremmer, J. N. Greek Religion and Culture, the Bible, and the Ancient Near East. (Jerusalem Studies in Religion and Culture, 8). Leiden, Boston, 235-248.Burges Watson, S. (2013). Orpheus: A Guide to Selected Sources. LivingPoets. Durham: https://livingpoets.dur.ac.uk/w/Orpheus:_A_Guide_to_Selected_Sources (11.11.2021).Clement of Alexandria (1919). The Exhortation to the Greeks. The Rich Man’s Salvation. To the Newly Baptized (fragment). Translated by G. W. Butterworth. (Loeb Classical Library, 92). Cambridge, MA.Deichgräber, K. (1939). Die Lykurgie des Aischylos, Versuch einer Wiederherstellung der dionysischen Tetralogie. (Nachrichten von der Gesellschaft der Wissenschaft der Wissenschaften zu Göttingen: Philologisch-historische Klasse, n.s. Fachgr. 1, N. F. Bd. 3, Nr 8). Göttingen: Vandenhoeck & Ruprecht, 231-309.Edmonds, J. M. (Ed.). (1959). The Fragments of Attic Comedy after Meineke, Begk, and Kock, Augmented, Newly Edited with their Contexts, Annotated, and Completely Translated into English Verse. Vol. II. Leiden.Euripides (1850). The Tragedies of Euripides, translated by T. A. Buckley. Bacchae. London: https://www.perseus.tufts.edu/hopper/text?doc=Eur.+Ba.+560&fromdoc=Perseus%3Atext%3A1999.01.0092 (23.02.2022).Euripides (1891). The Plays of Euripides, translated by E. P. Coleridge. Vol. I-II. London: http://www.perseus.tufts.edu/hopper/text?doc=Perseus%3Atext%3A1999.01.0120%3Acard%3D952 (23.02.2022).Euripides (1994). Euripides, with an English translation by David Kovacs. Cambridge: http://www.perseus.tufts.edu/hopper/text?doc=Perseus%3Atext%3A1999.01.0088%3Acard%3D328 (24.02.2022).Euripides (1995). Euripides, with an English translation by David Kovacs. Cambridge: http://www.perseus.tufts.edu/hopper/text?doc=Perseus%3Atext%3A1999.01.0106%3Acard%3D936 (24.02.2022).Faraone, C. A., & Obbink, D. (Eds.). (1991). Magika Hiera: Ancient Greek Magic and Religion. Oxford.Gesner, J. M. (Ed.). (1764). Orphei Argonautica, Hymni, Libellis de Lapidibus et Fragmenta. Lipsiae.Graf, F. (1987). Orpheus: a Poet among Men. In: Bremmer, J. (Ed.). Interpretations of Greek Mythology. London and Sydney, 80-106.Graf, F. (1994). Magic in the Ancient World. Translated by Franklin Philip. Cambridge, Mass.Graf, F. (2008). Tapping other powers. Magic in Greek and Roman Life. In: Μαγεία στην Αρχαία Ελλάδα, Εθνικό Ίδρυμα Ερευνών, Athina, 11-36.Heath, J. (1994). The Failure of Orpheus Author(s). – Transactions of the American Philological Association, Vol. 124, 163-196.Hermann, G. (1831). Aeschyli Tragoediae. Lipsiae.Hunter, R. (1989). Apollonius of Rhodes: Argonautica Book III. (Cambridge Greek and Latin Classics). Cambridge.Karanika, A. (2010). Inside Orpheus’ Songs: Orpheus as an Argonaut in Apollonius Rhodius’ Argonautica. – Greek, Roman, and Byzantine Studies, 50, 391-410.Kern, O. (1938). Die Religion der Griechen. Bd. 2. Berlin.Kingsley, P. (1995). Meetings with Magi: Iranian Themes among the Greeks, from Xanthos of Lydia to Plato’s Academy. – Journal of the Royal Asiatic Society of Great Britain and Ireland, 5, 173-210.Kock, T. (Ed.). (1884). Comicorum atticorum fragmenta. Vol. II, Pars I. Lipsiae.Krevans, N. (2000). On the Margins of Epic: the Foundation-Poems of Apollonius. In: Harder, M. A., Regtuit, R. F., Wakker, G. C. (Eds.). Apollonius Rhodius (= Helknistica Groningana, vol. 4), Leuven, Paris, 69-84.Linforth, I. M. (1931). Orpheus in the Bassarides of Aeschyls. – Transactions of the American Philological Association, 62, 11-17.Linforth, I. (1931a). Two Notes on the Legend of Orpheus. – Transactions and Proceedings of the American Philological Association, Vol. 62, 5-17.Lozanova-Stancheva, V. (2005). Der paratragische Tereus. In: Thrace in the Graeco-Roman World. Proceedings of the Xth International Congress of Thracology, Komotini-Alexandropoulis 18-23 October. Athens, 349-358.Lozanova-Stancheva, V. (2021). The Scene of “Orpheus Taming Wild Animals”: Orpheus and the Centaur Chiron. – After Constantine. Stories from the Late Antique and Early Byzantine Era, 1, 14-34.Meineke, A. (1839). Fragmenta Comicorum Graecorum. Vol. 1, Berolini.Nauck, A. (1839). Tragicorum graecorum fragmenta. Lipsiae.Nock, A. D. (1933). Paul and the Magus. In: Jackson, F. J., Lake, K. (Eds.). The Beginnings of Christianity. London, Vol. 5, 164-189.Nock, A. D. (1972). Paul and the Magus. In: Stewart, Z. (Ed.). Essays on Religion and the Ancient World. Oxford, 308-324.Nock, A. D. (1972a). Greeks and Magi. In: Stewart, Z. (Ed.). Essays on Religion and the Ancient World. Oxford, 516-526.Pickard-Cambridge, A. W. (1927). Dithyramb, Tragedy and Comedy. Oxford.Pearson, A. C. (1917). The Fragments of Sophocles. Vol. 2, Cambridge.Rives, J. B. (2002). Magic in the XII Tables Revisited. – Classical Quarterly, 52 (1), 270-90.Sansone, D. (1985). Orpheus and Eurydice in the Fifth Century. In: Classica et Medievalia, Revue danoise de Philologie et d’histoire. Vol. 36, Copenhagen, 53-64.Schoeller, F. M. (1969). Darstellungen des Orpheus in der Antike. Diss. Phil., Freiburg.Simonides (2014). Living Poets. A new approach to Ancient Poetry. Published on 24.02.2014. – https://livingpoets.dur.ac.uk/w/Simonides,fragment_62(PMG_567_Page (11.11.2021).Sistakou, E. (2008). Beyond the Argonautica: In Search of Apollonius’ Ktisis Poems. In: Papaghelis, T., Rengakos, A. (Eds.). Brill’s Companion to Apollonius Rhodius (second, revised ed.). Leiden, Boston, 311-340.Stansbury-O’Donnell, M. D. (1990). Polygnotos’s Nekyia: A Reconstruction and Analysis. – American Journal of Archaeology, 94 (2), 213-235.Stephens, S. (2008). Ptolemaic Epic. In: Papaghelis, T., Rengakos, A. (Eds.). Brill’s Companion to Apollonius Rhodius (second, revised ed.). Leiden, Boston, 96-97.Welcker, F. G. W. (1941). Die griechischen Tragödien: mit Rücksicht auf den epischen Zyklus geordnet. Vol. 3, Bonn.Wilamowitz-Moellendorf, U. von (1932). Der Glaube der Hellenen. Vol. II. Berlin.Wiles, D. (2005). (HY]Ψ[IPYLE. A version for the stage. In: McHardy, F., Robson, J. and Harvey, D. (Eds.). Lost Dramas of Classical Athens. Greek Tragic Fragments. Exeter, 189-207.Ziegler, K. (1939). Orpheus. – Realencyclopädie der classischen Altertumswissenschaft, Bd. 18.1, Sp. 1268-1293.
Keywords: Orpheus; Old Attic Theater; Otherness; Aristotle; Poetics